2009
DOI: 10.1017/s1751731109004868
|View full text |Cite
|
Sign up to set email alerts
|

Ovariohysterectomy alters body composition and adipose and skeletal muscle gene expression in cats fed a high-protein or moderate-protein diet

Abstract: The objective of this study was to measure changes in body composition, physical activity and adipose and skeletal muscle gene expression of cats fed a high-protein (HP) diet or moderate-protein (MP) diet, following ovariohysterectomy. Eight cats were randomized onto HP or MP diets and were fed those diets for several months prior to baseline. All cats underwent an ovariohysterectomy at baseline (week 0) and were allowed ad libitum access to dietary treatments for 24 weeks. Food intake was measured daily, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
23
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 44 publications
(62 reference statements)
5
23
1
Order By: Relevance
“…Food intake and body fat were increased after gonadectomy regardless of diet, but food intake tended to be greater in cats fed the high-protein diet. In agreement with previous findings (Belsito et al, 2009), voluntary physical activity level of the cats decreased during the light (9.6 activity counts/15-s epoch) and dark (11.9 activity counts/15-s epoch) periods 24 wk after spaying compared with baseline (28.0 and 35.9 activity counts/15-s epoch, respectively; Vester et al, 2009b). In that study, mRNA transcript abundance in adipose and skeletal muscle tissues was affected by BW gain but not by dietary treatment.…”
Section: Feline Studiessupporting
confidence: 92%
See 1 more Smart Citation
“…Food intake and body fat were increased after gonadectomy regardless of diet, but food intake tended to be greater in cats fed the high-protein diet. In agreement with previous findings (Belsito et al, 2009), voluntary physical activity level of the cats decreased during the light (9.6 activity counts/15-s epoch) and dark (11.9 activity counts/15-s epoch) periods 24 wk after spaying compared with baseline (28.0 and 35.9 activity counts/15-s epoch, respectively; Vester et al, 2009b). In that study, mRNA transcript abundance in adipose and skeletal muscle tissues was affected by BW gain but not by dietary treatment.…”
Section: Feline Studiessupporting
confidence: 92%
“…Along with BW gain, relative gene expression of IL-6 was increased (wk 0 = 210 ± 18 AU and wk 24 = 463 ± 71 AU) in adipose tissue whereas gene expression of LPL (wk 0 = 968 ± 159 AU and wk 24 = 543 ± 50 AU), HSL (wk 0 = 702 ± 120 AU and wk 24 = 436 ± 49 AU), and adiponectin (wk 0 = 1,070 ± 335 AU and wk 24 = 460 ± 124 AU) were decreased at wk 24 when compared with baseline (Belsito et al, 2009). Another study from our laboratory investigated the effects of ovariohysterectomy on body composition, blood metabolite concentrations, voluntary physical activity level, and mRNA transcription in subcutaneous adipose and skeletal muscle tissues of cats fed either a high-protein [i.e., 53% CP and 10% nitrogen free extract (NFE)] or a moderate-protein (i.e., 34% CP and 34% NFE) diet (Vester et al, 2009b). Food intake and body fat were increased after gonadectomy regardless of diet, but food intake tended to be greater in cats fed the high-protein diet.…”
Section: Feline Studiesmentioning
confidence: 99%
“…Previous research in our laboratory indicated greater fasting leptin concentrations in moderate‐protein fed adult cats compared with high‐protein fed adult cats (same diets as current study) (Vester et al . 2009b).…”
Section: Discussionsupporting
confidence: 59%
“…Similarly, post-neuter changes in energy expenditure have also been suggested in other species [11]. Evidence also exists that cats consume more if fed ad libitum [12, 13]. Irrespective of whether energy consumption or expenditure is the major driver of neuter-associated weight gain, weight gain is likely to be a consequence of the disruption in the cat’s endocrine milieu.…”
Section: Introductionmentioning
confidence: 96%